2021
DOI: 10.1002/jat.4235
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics approach to study in vivo toxicity of graphene oxide nanosheets

Abstract: Although graphene oxide (GO) nanosheets are widely used in different fields, the mechanism of their toxicity remains relatively unknown. NMR‐based metabolomics was used to study in vivo time and dose‐dependent toxicity of GO nanosheets in mice. Sixty serum samples from mice in four different time intervals including 24 and 72 h and 7 and 21 days after injection of 0‐, 1‐, and 10‐mg/kg b.w. were analyzed based on 1HNMR spectra of each sample and multivariate methods. In comparison with the control group, 12 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The adsorption of steroid hormones on GO nanosheets is a good example, where hydrophobic and electrostatic interactions present in long‐range up to 10 nm and short ranges (2–5 nm) interactions include π – π stacking, van der Waals forces, and hydrogen bonding. [ 134 ] Several groups adapted self‐assembly to connect DNA, [ 131 ] SS‐GrBP5 mutant, [ 10 ] polyoxyethylene sorbitan laurate (TWEEN 20), [ 126 ] and photoreceptor proteins [ 17 ] to graphene.…”
Section: Functionalization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption of steroid hormones on GO nanosheets is a good example, where hydrophobic and electrostatic interactions present in long‐range up to 10 nm and short ranges (2–5 nm) interactions include π – π stacking, van der Waals forces, and hydrogen bonding. [ 134 ] Several groups adapted self‐assembly to connect DNA, [ 131 ] SS‐GrBP5 mutant, [ 10 ] polyoxyethylene sorbitan laurate (TWEEN 20), [ 126 ] and photoreceptor proteins [ 17 ] to graphene.…”
Section: Functionalization Methodsmentioning
confidence: 99%
“…Researchers aim to develop a method that overcomes the limitations of the lack of organ donors, disease transmission, and immune reactions using regenerated tissue produced with biocompatible scaffolds. [ 116–175 ] Materials used for tissue engineering need to be biocompatible as well as without inducing immune reactions (not toxic). Graphene materials can be applied as substrates due to their unique electrical and mechanical properties.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo toxic effects of 2D biomaterials have been systematically studied, such as graphene and black phosphorus. 133,134 However, systematical research on the in vivo toxicity of metallenes is rarely carried out. Based on the present research, more attention should be paid to the in vivo toxicity of metallenes for promoting their biomedical applications.…”
Section: Toxicitymentioning
confidence: 99%
“…The toxicity of graphene and its derivatives in cells depends on several factors, including the exposure dose, exposure time, and physicochemical properties of graphene and its derivatives. In vivo animal toxicity tests have shown that the main routes of exposure to graphene and its derivatives include oral administration (Yu et al, 2019), inhalation, and injection (Ghiasvand Mohammadkhani et al, 2022; Ruiz et al, 2020). After oral and nasal inhalation or intratracheal, intravenous, or peritoneal administration, graphene and its derivatives can be further transferred through the circulatory system across the blood–brain barrier and tend to accumulate in the liver, lungs, kidneys, and brain, inducing granulomas in the liver, kidneys, lungs, and spleen of mice (Devasena et al, 2021).…”
Section: Introductionmentioning
confidence: 99%